Aggravation of hepatic encephalopathy after portosystemic shunting interventions (TIPS procedure) for complicated portal hypertension - Yu. V. Khoronko; A. V. Blikyan; M. A. Kozyrevskiy (Медицинский вестник Юга России, 2018)
Objective.  Creation of portosystemic shunts (TIPS operation) leads frequently to aggravation of hepatic encephalopathy (HE). Aim of the study is to improve results of prophylaxis and treatment of HE after TIPS procedure in patients with complications of portal hypertension due to liver cirrhosis.Material and Methods. 207 patients underwent TIPS procedure in our clinic in 2007-17. Indications for TIPS placement were life-threatening complications of portal hypertension: variceal esophageal bleeding (in 156) and refractory ascites (in 51). Patients were divided in 3 groups comparable by main clinical characteristics. Indexes of portal hemodynamics, such as pre- and post-TIPS blood pressure in portal vein, and portosystemic gradient (PSG) were studied.Results. Overall, post-TIPS HE within 6 weeks was different in each of 3 groups: 29,3% at 1st, 18,8% at 2nd, 13,2% at 3rd as result of individual algorithm of treatment based on intensive measures of complex treatment at 2nd and 3rd groups. High prognostic value of pre-TIPS PSG more than 18 mm Hg and difference between pre- and post-TIPS PSG more than 8 mm Hg was established. It required more intensive therapy in 2nd and 3rd groups which resultedConclusions. Aggravation of post-TIPS HE is a predictable complication. Level of pre-TIPS PSG more than 18 mm Hg is associated with an increased risk of HE. The correlation of difference between pre- and post-TIPS PSG more than 8 mm Hg and post-TIPS HE was revealed also. It demands more intensive measures of prophylaxis and treatment. Inclusion of serotonin to treatment’s programme allows us to improve the elimination of products of gut micribiota by regulating of intestinal motility.